DOI: 10.31274/rtd-180815-103
|View full text |Cite
|
Sign up to set email alerts
|

Early family experiences and the financial behavior of college students: the impact of gender and gambling

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A greater scale specifies greater investment awareness for the respondents. The measurements of independent variables are as follows: The measures for financial literacy (FL) (11 items) have been adapted from the studies of [21,38,91,92]; Spending patterns (SP) are measured with five items that are adopted from [93]; The seven items used to measure self-control (SC) have been adapted from [14,64]; The scales used for measuring saving behavior (SB) (eight items) were adapted from prior work [10,21,71]; Attitude toward risk (AtR) was measured by 13 items that have been adapted from the previous work of [25,78,90,94,95]; Finally, family financial socialization (FFS) was measured by six items that have been adopted from the previous work of [21,71]. The responses to all survey items were scored on a five-point Likert scale, which ranges from (1) "strongly disagree" to (5) "strongly agree."…”
Section: Measurementmentioning
confidence: 99%
“…A greater scale specifies greater investment awareness for the respondents. The measurements of independent variables are as follows: The measures for financial literacy (FL) (11 items) have been adapted from the studies of [21,38,91,92]; Spending patterns (SP) are measured with five items that are adopted from [93]; The seven items used to measure self-control (SC) have been adapted from [14,64]; The scales used for measuring saving behavior (SB) (eight items) were adapted from prior work [10,21,71]; Attitude toward risk (AtR) was measured by 13 items that have been adapted from the previous work of [25,78,90,94,95]; Finally, family financial socialization (FFS) was measured by six items that have been adopted from the previous work of [21,71]. The responses to all survey items were scored on a five-point Likert scale, which ranges from (1) "strongly disagree" to (5) "strongly agree."…”
Section: Measurementmentioning
confidence: 99%
“…Individuals with such a trait also exhibit a propensity to make risky financial investments (Harlow & Brown, 1990). A few studies have investigated the relationship of sensation seeking with financial management behaviour, especially the use of credit card in particular (e.g., Henry, Weber, & Yarbrough, 2001;Miller, 2001;Popham, Kennison, & Bradley, 2011;Worthy, Jonkman, & Blinn-Pike, 2010). They found that students exhibited risky financial behaviour such as accumulating more debt, overdrawing their accounts, borrowing money from their friends to pay their bills and so on.…”
Section: Relationship Between Sensation Seeking (Ss) and Frtmentioning
confidence: 99%